Method for producing fine copper oxide-containing particles, and fine copper oxide-coated copper particles
By mixing the copper oxide raw material particles containing CuO and Cu2O on the surface with a solution of an amine-based compound and a complexing agent, and reacting in an oxygen-containing atmosphere, the problems of reaction control and particle size control in the prior art are solved, and the low-temperature sintering and uniform dispersion of Cu64O and Cu8O are achieved, and efficient manufacturing of micro-oxide copper particles is achieved.
Patent Information
- Application Number
- CN202380061155.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-09
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when producing copper oxide-containing particles, copper salts such as copper acetate are used as starting materials, resulting in large volume and heavy weight, the reaction process takes a long time, and in a high concentration system, reaction control and particle size control are difficult, making it difficult to obtain a state of uniform dispersion of micro-copper oxide and metal copper particles.
By preparing raw material particles containing CuO and Cu2O at least on the surface, mixing them with a solution containing an amine-based compound and a complexing agent, adding a reducing agent, and reacting in an oxygen-containing atmosphere, low-temperature sintering of Cu64O and Cu8O is achieved.
A manufacturing method with good mass production is realized, and Cu64O and Cu8O can be sintered at a low temperature below 150°C, solving the problems of reaction control and particle size control in the prior art, and obtaining a state of uniform dispersion of micro-copper oxide and metal copper particles.
Smart Images

Figure CN119768242A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing micro-copper oxide-containing particles and micro-copper oxide-coated copper particles. Background Art
[0002] In recent years, in the manufacture of printed circuit boards, a technology called printed electronics, which directly forms fine wiring by inkjet or printing, has attracted attention as a clean technology that does not require conventional exposure and etching and does not emit harmful chemicals.
[0003] The above-mentioned fine wiring is mainly obtained by heating metal particles to sinter them. From the perspective of heat resistance of the substrate, for example, the metal particles are required to be sintered at a low temperature below 150°C. The current situation is that silver particles that can be sintered at low temperatures are widely used, but silver particles are expensive and may cause wiring short circuits due to ion migration. As an alternative to silver particles, copper particles that are cheap and highly resistant to ion migration have attracted attention, but there is a problem that copper particles are difficult to sinter at low temperatures.
[0004] In order to solve the above problems, the present inventors tried to obtain low temperature sintering particles using copper oxides. As copper oxides, CuO, Cu 2 O, Cu 4 O 3 , Cu 8 O and Cu 64 O five kinds. Among them, Cu 64 O and Cu 8 O with CuO and Cu as stable phases 2 O has a smaller proportion of oxygen atoms and lower stability, and can be reduced to metallic copper with low energy. 64 O and Cu 8 O can achieve low temperature sintering below 150°C. In this specification, Cu with a small proportion of oxygen atoms is 64 O and Cu 8 O is called "micro-oxide copper" to make it compatible with other oxides such as CuO and Cu 2 O, Cu 4 O 3 To distinguish.
[0005] For example, Patent Document 1 discloses an oxide-containing copper microparticle containing Cu 64 O and Cu as required 2 O and copper oxide particles coated with carboxylic acid, wherein Cu 64 The mass of O is relative to Cu and Cu 64 O and Cu 2 The total mass ratio of O is 0.5 to 2.0 mass %.
[0006] In recent years, electrical components are required to have better electrical conductivity. As a conductive material technology utilizing the reduction of the melting point of nanometer-sized particles, there are not only copper particles containing submicron oxides whose surface necking characteristics are improved by carboxylic acid coating as described in Patent Document 1, but also the following Patent Documents 2 and 3. Patent Document 2 discloses a copper oxide particle composition comprising Cu 64 O particles and Cu 8 O particles, the Cu 64 O particles and the Cu 8 At least one of the O particles has an average particle size of 20 nm or less. Patent Document 3 discloses a mixed particle comprising a copper cluster having an average particle size of 0.1 nm or more and 1 nm or less, and a copper oxide particle having an average particle size of more than 1 nm and 20 nm or less, wherein the copper oxide particle is Cu 64 O particles and the Cu 8 In addition, Patent Document 3 discloses a mixed particle comprising: a copper cluster having an average particle size of 0.1 nm or more and 1 nm or less; a copper oxide particle having an average particle size of more than 1 nm and less than 20 nm; and a metal copper particle having an average particle size of more than 20 nm and less than 1 μm. The copper oxide particle is Cu 64 O particles and the Cu 8 At least one of the O particles.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Literature : International Publication No. 2022 / 045252
[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-29392
[0011] Patent Document 3: Japanese Patent Application Publication No. 2020-100893 Summary of the invention
[0012] Problems to be solved by the invention
[0013] In Patent Document 2 and Patent Document 3, although the manufacture of the copper oxide particles contained in the mixed particles uses copper salts such as copper acetate as the starting raw material, the copper salt is large in volume and heavy in weight, and the reaction process including the dissolution of the copper salt in the solvent takes a long time. In addition, although the concentration of copper ions is high at the beginning of the reduction, since the concentration changes during the reaction, it is difficult to control the reaction and the resulting particle size, especially in a concentrated system. Therefore, it is believed that further research is needed for industrial mass production. In addition, in the obtained mixed particles, the metallic copper particles and the fine copper oxide particles are each easily agglomerated, and it is difficult to obtain a state in which they are dispersed with each other. In view of the above situation, one of the purposes of the present invention is to provide a method for manufacturing a Cu 2+ mixed particle having a surface that can be used for sintering at low temperature with good mass production performance. 64 O and Cu 8 A method for producing micro-oxide copper-containing particles containing at least one micro-oxide copper in O.
[0014] Means of solving the problem
[0015] A first aspect of the present invention is a 64 O and Cu 8 A method for producing micro-oxide copper-containing particles containing at least one micro-oxide copper in O, comprising:
[0016] Prepare a material having at least CuO and Cu on the surface 2 O or more copper oxide raw material particles; and
[0017] The raw material particles are mixed with a solution containing an amine compound and a complexing agent, and then a reducing agent is added to carry out a reaction in an oxygen-containing atmosphere.
[0018] Aspect 2 of the present invention is a production method according to aspect 1, wherein the raw material particles are made of CuO and Cu 2 O is composed of raw material particles consisting of one or more copper oxides.
[0019] A third aspect of the present invention is the production method according to the first aspect, wherein the raw material particles are copper oxide-coated copper raw material particles, which have copper raw material particles as cores and contain CuO and Cu 2 One or more copper oxide films among O are the shell.
[0020] Aspect 4 of the present invention is the production method according to any one of aspects 1 to 3, wherein the copper oxide contained in the raw material particles is Cu 2 O.
[0021] Aspect 5 of the present invention is the production method according to any one of aspects 1 to 4, wherein the complexing agent is a carboxylic acid.
[0022] Aspect 6 of the present invention is the production method according to any one of aspects 1 to 5, wherein the complexing agent is acetic acid.
[0023] Aspect 7 of the present invention is the production method according to any one of aspects 1 to 6, wherein the reaction is performed at 50° C. or lower.
[0024] Aspect 8 of the present invention is the production method according to any one of aspects 1 to 7, wherein the average particle size of the raw material particles is higher than 20 nm and not more than 10 μm.
[0025] A ninth aspect of the present invention is a slightly oxidized copper-coated copper particle having a copper particle as a core and containing Cu 64 O and Cu 8 O has a shell of more than one micro-oxidized copper.
[0026] Aspect 10 of the present invention is the slightly-oxidized copper-coated copper particle according to aspect 9, wherein the Cu 64 O and Cu 8 The one or more micro-copper oxide particles in O are micro-copper oxide particles having an average particle size greater than 1 nm and less than 20 nm.
[0027] Aspect 11 of the present invention is the slightly copper-oxide-coated copper particle according to aspect 9 or 10, wherein the copper particles serving as the core have an average particle diameter of more than 20 nm and not more than 2 μm.
[0028] A twelfth aspect of the present invention is a bonding material comprising the slightly-oxidized copper-coated copper particles according to any one of aspects 9 to 11.
[0029] Effects of the Invention
[0030] According to the present invention, it is possible to provide a method for producing a Cu-based substrate having at least a surface that can be sintered at a low temperature with good mass productivity. 64 O and Cu 8 A method for producing micro-oxide copper-containing particles containing at least one micro-oxide copper in O. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is the XRD spectrum of the reaction process of Examples 1 to 3.
[0032] Figure 2 It is the XRD spectrum of the reaction process of Comparative Examples 1-3.
[0033] Figure 3 It is the XRD spectrum of Comparative Examples 4-6 during the reaction process.
[0034] Figure 4 These are TEM images of particles obtained in Examples 1 to 3.
[0035] Figure 5 Example 1 (starting material Cu 2 O) STEM image of the particles obtained.
[0036] Figure 6 This is a STEM image of the particles obtained in Example 2 (starting material CuO).
[0037] Figure 7 It is the XRD spectrum of the reaction process of Examples 4 to 6.
[0038] Figure 8 It is the XRD spectrum of Examples 7, 8 and Comparative Example 7 during the reaction process.
[0039] Fig. 9 These are SEM images of the starting material of Example 4 and the particles after 24 hours of reaction.
[0040] Fig.10 This is a TEM image of the particles obtained in Example 4.
[0041] Fig.11 These are STEM images of particles obtained in Example 4. The STEM image on the right is an enlarged image of the lattice plane spacings of the particles shown in the STEM image on the left.
[0042] Fig.12 These are SEM images of the starting material of Example 5 and the particles after 24 hours of reaction.
[0043] Fig.13 This is a TEM image of the particles obtained in Example 5.
[0044] Fig.14 This is a TEM image of the particles obtained in Example 6.
[0045] Fig.15 These are SEM images of the starting material of Example 7 and the particles after 24 hours of reaction.
[0046] Fig.16 This is a TEM image of the particles obtained in Example 7.
[0047] Fig.17 These are SEM images of the starting material of Example 8 and the particles after 24 hours of reaction.
[0048] Fig.18 This is the TG-DTA measurement result of Example 4A.
[0049] Fig.19 It is a diagram showing the process of preparing the sample for evaluation of the bonding firing in Example 4A.
[0050] Fig. 20AThis is a schematic diagram of a copper test piece used to prepare a sample for evaluation of bonding firing in Example 4A.
[0051] Fig. 20B This is a schematic diagram of a metal mask used for preparing a sample for evaluation of bonding firing in Example 4A.
[0052] Fig. 20C It is a schematic diagram explaining the hot press machine in the bonding firing evaluation test of Example 4A.
[0053] Fig.20D It is a schematic cross-sectional view for explaining the method of the bonding firing evaluation test of Example 4A.
[0054] Fig.21 It is a graph showing the results of the bonding firing evaluation test of Example 4A.
[0055] Fig. 22 This is a SEM image of the fracture surface observed after the bonding firing evaluation test of Example 4A.
[0056] Fig.23 This is the temperature distribution of the hot press when the bonding time of Example 4A is 1 minute.
[0057] Fig.24 It is a graph showing the conductivity evaluation results of Example 4A.
[0058] Fig.25 This is the XRD spectrum of the paste before and after firing in the conductivity evaluation of Example 4A.
[0059] Fig.26 This is a SEM image of the fired product in the conductivity evaluation of Example 4A.
[0060] Fig. 27 This is the XRD pattern during the reaction of Example 9.
[0061] Fig.28 These are SEM images of the starting material of Example 9 and the particles after 24 hours of reaction.
[0062] Fig.29 This is a TEM image of the particles obtained in Example 9. DETAILED DESCRIPTION
[0063] The present inventors have aimed to manufacture a Cu-based composite having at least a surface that can be sintered at a low temperature with good mass productivity. 64 O and Cu 8 As a result, it was found that it is important to prepare particles having at least one of CuO and Cu 2O; and in the manufacturing process, the raw material particles are mixed with a solution containing a complexing agent. In addition, the present inventors have also found a micro-copper oxide coated copper particle, which has a copper particle as a core and a copper particle containing Cu 64 O and Cu 8 O. First, the production method of this embodiment will be described in detail.
[0064] [At least Cu 64 O and Cu 8 O] A method for producing particles containing slightly oxidized copper having at least one slightly oxidized copper in the
[0065] In this embodiment, the Cu 64 O and Cu 8 A method for producing micro-oxide copper-containing particles containing at least one micro-oxide copper in O, comprising:
[0066] Prepare a material having at least CuO and Cu on the surface 2 O or more copper oxide raw material particles; and
[0067] The raw material particles are mixed with a solution containing an amine compound and a complexing agent, and then a reducing agent is added to carry out a reaction in an oxygen-containing atmosphere.
[0068] The production method of the present embodiment can be divided into the following first production method and second production method according to the form of raw material particles.
[0069] The first manufacturing method is to contain Cu 64 O and Cu 8 A method for preparing micro-oxidized copper particles containing at least one micro-oxidized copper in CuO, comprising: 2 O are used as raw material particles, the raw material particles are mixed with a solution containing an amine compound and a complexing agent, and then a reducing agent is added to carry out a reaction.
[0070] The second manufacturing method comprises a copper particle as a core and a 64 O and Cu 8 A method for preparing core-shell type micro-oxide copper-coated copper particles having a shell of at least one micro-oxide copper in CuO, comprising: using a copper raw material particle as a core and 2 Copper oxide-coated copper raw material particles having one or more copper oxide films as a shell are used as raw material particles, and the raw material particles are mixed with a solution containing an amine compound and a complexing agent, and then a reducing agent is added to perform a reaction.
[0071] Hereinafter, the conditions of the production method of this embodiment will be described in detail.
[0072] [Process of preparing raw material particles]
[0073] First, prepare a substrate having at least CuO and Cu on the surface. 2 In the first production method, as the raw material particles, a raw material particle containing CuO and Cu 2 O. The raw material particles may contain CuO and Cu 2 O. The raw material particles of the first production method preferably contain Cu 2 O copper oxide raw material particles.
[0074] In the second production method, copper oxide-coated copper raw material particles are prepared as the raw material particles, wherein the copper raw material particles are used as cores and the raw material particles contain CuO and Cu 2 The particles may be core-shell copper oxide-coated copper raw material particles, which have a copper raw material particle as a core and are preferably coated with a copper oxide film containing CuO and Cu 2 O, preferably a coating containing Cu 2 O of copper oxide.
[0075] The copper oxide-coated copper raw material particles used as raw material particles in the second manufacturing method may be commercially available, or may be particles formed with a surface oxide film by natural oxidation of copper particles, or may be particles formed with a surface oxide film by oxidation treatment of the surface of copper particles. Alternatively, copper oxide-coated copper raw material particles obtained as follows may be used, and a copper oxide-coated copper raw material particle containing CuO and Cu may be added to the surface of a copper raw material particle on which copper oxide is not formed at all or is hardly formed. 2 O) is obtained by, for example, adding to a dispersion containing the copper raw material particles or supplying by coating or the like. In addition, the surface oxide film formed by natural oxidation is formed only by the presence of the metal copper particles in the atmosphere. Therefore, it can be considered that the commercially available metal copper particles are also naturally oxidized in the atmosphere, and the particles on which the surface oxide film is formed by natural oxidation of the copper particles as the raw material particles of the second manufacturing method also include the commercially available metal copper particles.
[0076] In the production method of this embodiment, the size of the raw material particles is not limited. In the case of the first production method, the raw material particles containing CuO and Cu 2 The raw material particles of one or more copper oxides among CuO and CuO may have an average particle size of, for example, 20 nm to 10 μm.2 From the viewpoint that CuO remains as a residue, the average particle size of the raw material particles in the first manufacturing method is preferably 10 μm or less as described above. In the case of the second manufacturing method, the average particle size of the copper raw material particles as the core can be, for example, 20 nm to 2 μm. In addition, the copper raw material particles as the core contain CuO and Cu 2 O, the film thickness can be 20nm or less. In this specification, "particle size" refers to the primary particle size and equivalent circle diameter, and "average particle size" refers to the median diameter of more than 150 particles randomly selected from SEM images or TEM images.
[0077] In the second production method, the CuO and Cu 2 O, one or more copper oxides (preferably including Cu 2 The copper oxide film of the raw material particles may be more than the natural oxide film. For example, the copper oxide film containing CuO and CuO occupies the raw material particles. 2 The proportion of one or more copper oxides in O may be 1 mass % or more. If the core-shell type micro-copper oxide coated copper particles to be finally obtained are to be formed thickly, the copper oxide containing Cu 64 O and Cu 8 O, the raw material particles can be actively oxidized. In this case, if too much copper oxide occupies the surface of the raw material particles, the Cu 64 O and Cu 8 O, it is difficult for the shell of one or more micro-oxidized copper particles to adhere to the copper particles as the core. 64 O and Cu 8 O, the shell of one or more micro-oxidized copper particles in the raw material particles has lower crystallinity than the copper particles as the core particles with high crystallinity. Therefore, if the shell is thick, the mechanical strength and electrical conductivity may be reduced. From these viewpoints, the raw material particles containing CuO and Cu 2 The ratio of one or more copper oxides in O is preferably 10 mass % or less.
[0078] 〔Reaction process〕
[0079] The raw material particles are mixed with a solution containing an amine compound and a complexing agent, and then a reducing agent is added to carry out a reaction. As mentioned above, the complexing agent and the like required for the reaction are described below.
[0080] (Complexing agent)
[0081] In this embodiment, the copper oxide contained in the raw material particles is reacted with a complexing agent to form a copper complex ion. In this way, by ionizing the copper in the raw material particles, the reduction rate of the reducing agent can be significantly faster than the solid copper oxide reduction. As the complexing agent, carboxylic acids can be cited. As carboxylic acids, for example, formic acid, saturated fatty acids, unsaturated fatty acids, hydroxy acids, aromatic carboxylic acids, terpene carboxylic acids, etc. can be cited. It can be a monocarboxylic acid or a dicarboxylic acid. In addition, it can be used alone or in combination of two or more. The aliphatic monocarboxylic acid can be either straight-chain or branched, and can also be any one of a saturated aliphatic monocarboxylic acid and an unsaturated aliphatic monocarboxylic acid. As straight-chain saturated aliphatic monocarboxylic acid, acetic acid (carbon number 2), propionic acid (carbon number 3), butyric acid (carbon number 4), valeric acid (carbon number 5), hexanoic acid (carbon number 6), etc. can be cited.
[0082] The aliphatic dicarboxylic acid may be straight-chain or branched, and may be any of a saturated aliphatic dicarboxylic acid and an unsaturated aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid may be used alone or in combination of two or more. Examples of the aliphatic dicarboxylic acid include adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,0-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, tridecanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,13-tridecanedicarboxylic acid, tapixic acid, 1,15-pentadecanedicarboxylic acid, 1,16-hexadecanedicarboxylic acid, and 1,16-hexadecanedicarboxylic acid. Aromatic carboxylic acids include benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, 1,2,3-benzenetricarboxylic acid, trimellitic acid, trimesic acid, etc. As terpene carboxylic acids, those contained in rosin, etc. can be used. For example, abietic acid, neoabietic acid, palustric acid, pimaric acid, isopimaric acid, dehydroabietic acid, etc. can be mentioned.
[0083] Among them, acetic acid is preferably used because it is easy to handle and can be easily handled after the reaction.
[0084] The amount of the complexing agent added to the reaction is not particularly limited, but in order to promote the 64 O and Cu 8 The generation of O is preferably 2 times or more and 15 times or less in molar ratio to the copper contained in the starting material particles from the viewpoint of promoting the formation of copper complex ions.
[0085] (Amine compounds)
[0086] A compound having an amino group (hereinafter referred to as an "amine compound") is added as a protective agent. The amine compound also contributes to the complex ion formation of copper. The amine compound is not particularly limited, and for example, alkanolamines, diamines, and aminocarboxylic acids are preferably used. Among them, alkanolamines are more preferably used. As alkanolamines, for example, 2-amino-1-butanol, 1-amino-2-propanol, 2-amino-2-ethyl-1,3-propanediol, 2-amino-2-hydroxymethyl-1,3-propanediol, 1,3-diamino-2-propanol, 1-amino-2-butanol, 2-aminoethanol, etc. can be cited.
[0087] The amount of the amine compound added for the reaction is not particularly limited, but 64 O and Cu 8 From the viewpoint of the formation of O, the molar ratio of the amine compound to the copper contained in the raw material particles is preferably 5 times or more. The molar ratio may be, for example, 20 times or less.
[0088] (Solvent)
[0089] The solvent is not particularly limited, and for example, polyols such as ethylene glycol, lower alcohols such as methanol, ethanol, and 2-propanol, ketones such as acetone, and water can be used.
[0090] (reducing agent)
[0091] The reducing agent is not particularly limited, and hydrazine-based reducing agents such as hydrazine, hydrazine hydrochloride, hydrazine sulfate, and hydrazine hydrate, citric acid, ascorbic acid, borohydride salts such as sodium borohydride, etc. can be used. The reducing agent can be added after the raw materials containing the above-mentioned raw material particles, complexing agent, amine compound and solvent are added and mixed. After the reducing agent is added, in the first manufacturing method, stirring is performed until at least the raw material particles disappear, and in the second manufacturing method, stirring is performed until the desired micro-oxide copper is confirmed to be formed. Regardless of which manufacturing method, it is preferably stirred until the reducing agent disappears to allow it to react fully.
[0092] (Cooling during reaction)
[0093] In the production method of this embodiment, for example, when hydrazine is used as a reducing agent, the addition of the reducing agent may generate heat due to the decomposition reaction of hydrazine, and the temperature of the reaction solution may rise. By suppressing the temperature rise of the reaction solution, the Cu 64 O and Cu 8 From the viewpoint of reducing O to metallic copper, it is preferred to provide a temperature control mechanism such as cooling the reaction solution so that the reaction proceeds at 50° C. or less. For example, as shown in the examples described below, the reducing agent is preferably added while the reaction container is immersed in water.
[0094] (Atmosphere during reaction)
[0095] In the manufacturing method of this embodiment, the reaction atmosphere is limited to an oxygen-containing atmosphere such as air, and the reaction needs to be always exposed to the oxygen-containing atmosphere. When the atmosphere is an inert gas such as nitrogen or argon, or when the reaction container is sealed even in the air, the oxide Cu is formed. 64 O or Cu 8 The reaction of O does not progress, but metal copper particles are formed, which is not preferable.
[0096] (Other processes)
[0097] The manufacturing method of this embodiment may further include steps other than the above, for example, the step of reducing the Cu 64 O and Cu 8 O, such as a slurry of one or more micro-copper oxide particles, and subjecting the slurry to centrifugal separation or filtration to recover the micro-copper oxide particles, and may also include a subsequent purification step, a drying step, etc. In the purification step, it is preferred to purify by a washing solvent. The washing solvent is not particularly limited, and for example, an organic solvent such as N,N-dimethylacetamide, toluene, hexane, etc. can be used.
[0098] According to the first manufacturing method, as the 64 O and Cu 8 O containing slightly oxidized copper particles, in particular, can obtain particles containing Cu 64 O and Cu 8 O. The copper oxide particles having Cu obtained by the first manufacturing method 64 O and Cu 8 O containing slightly oxidized copper particles (preferably containing Cu 64 O and Cu 8 The average particle size of at least one micro-copper oxide particle (0) may be higher than 1 nm and below 20 nm. The average particle size may be further below 15 nm, and further below 10 nm.
[0099] According to the first manufacturing method, a composition containing micro-oxide copper particles can be obtained in which copper clusters having an average particle size of 0.1 nm to 1 nm coexist with the micro-oxide copper particles. The average particle size of the copper clusters can be further from 0.15 nm to 0.7 nm, and further from 0.17 nm to 0.5 nm. Such copper clusters are usually formed by the aggregation of about 3 to 6 copper atoms. As mentioned above, copper clusters are aggregates of a very small number of atoms and have an extremely small particle size, so they have a low melting point due to the nanosize effect. Therefore, such copper clusters have high sinterability.
[0100] In this embodiment, the obtained trace copper oxide-containing particles include Cu 64 O and Cu 8 O, this can be confirmed by STEM observation as shown in the examples described below. 64 O and Cu 8 The same goes for O.
[0101] [Micro-oxidized copper coated copper particles]
[0102] The slightly oxidized copper-coated copper particles of the present embodiment are provided with a copper particle as a core and a 64 O and Cu 8 O has a micro-oxide copper-coated copper particle. For example, as in the prior art, in Cu 64 O particles and Cu 8 In the composition of at least one micro-oxide copper particle, metal copper particle, and copper cluster among the O particles, it is difficult to uniformly disperse them. In particular, when the micro-oxide copper particles are microparticles with an average particle size of less than 20 nm, the microparticles are easily aggregated and difficult to disperse. In contrast, the micro-oxide copper-coated copper particles of this embodiment have a core-shell structure, that is, Cu 64 O and Cu 8 O is attached to the surface of the metal copper particles as the core in the form of a coating, thereby solving the above-mentioned dispersion problem. In addition, when the micro-oxidized copper-coated copper particles of this embodiment are sintered, the Cu 64 The sintering of the micro-oxide copper particles such as O is promoted, and a sintered body having high electrical conductivity can be easily produced.
[0103] The size of the copper particles constituting the core of the micro-oxide copper-coated copper particles of this embodiment is not limited, and for example, the average particle size may be 20 nm to 2 μm. The average particle size may also be higher than 20 nm. Although the average particle size may be higher than 2 μm, for example, when used in printed electronics, coarse particles may lead to reduced printing quality, so the average particle size is 2 μm or less.
[0104] Shell-forming Cu 64 O and Cu 8 O, the form of the micro-oxide copper may be a coating or a plurality of particles. When the particles are multiple particles, the average particle size of the particles may be, for example, 1 nm to 20 nm. The shell thickness (the thickness of the coating or the stacking thickness of the multiple particles) may be, for example, 1 to 20 nm. 64 O and Cu 8 The shell of one or more micro-oxidized copper particles in O is reduced to copper after sintering, but its crystallinity is not as high as that of the copper particles as the core, so if the shell is too thick, the mechanical strength and conductivity may be reduced. From these viewpoints, the thickness of the shell is preferably 20 nm or less as described above.
[0105] In addition to Cu 64 O and Cu 8 In addition to one or more trace amounts of copper oxides among O, trace amounts of CuO, CuO used as raw materials, etc. are also permitted at a level that does not impair sinterability and electrical conductivity. 2 O and other copper oxides. It is preferred that the raw material does not contain CuO, Cu 2 The shell is preferably made of copper oxide containing Cu 64 O and Cu 8 O is formed by one or more micro-oxidized copper, preferably comprising Cu 64 O, or containing Cu 64 O and Cu 8 O forms micro-oxide copper.
[0106] The slightly copper-oxide-coated copper particles can be produced by the second production method described above, but are not limited thereto and may be produced by a method different from the second production method.
[0107] The slightly oxidized copper-coated copper particles of this embodiment have Cu on the surface. 64 O and Cu 8O, thus having high sinterability. That is, if the slightly oxidized copper-coated copper particles of this embodiment are used, a fully sintered sintered body can be obtained even at normal pressure (or pressure above it), at a relatively low temperature of 250°C or less, even at 200°C or less, even at 150°C or less, and even at a relatively low temperature of room temperature to 130°C. In addition, the slightly oxidized copper-coated copper particles of this embodiment have a core portion of metallic copper, and CuO and Cu 2 Since the content of copper oxide such as O which may increase the resistance is suppressed, a sintered body showing high electrical conductivity can be obtained by sintering the slightly copper-oxide-coated copper particles.
[0108] Examples of the sintering material include a paste or ink containing the slightly oxidized copper-coated copper particles of the present embodiment for the purpose of forming a conductive film, etc. The dispersion medium, binder, etc. contained in the paste or ink may be known materials.
[0109] The present invention also includes a bonding material containing the micro-copper oxide coated copper particles of the present embodiment. As the bonding material, a paste or ink containing the micro-copper oxide coated copper particles of the present embodiment can be cited. The dispersion medium, adhesive, etc. contained in the paste or ink can use known materials. The bonding material containing the micro-copper oxide coated copper particles of the present embodiment can be bonded to the bonding surface of various materials, such as metals (pure metals, alloys), ceramics, etc., for example, by coating, to obtain a bonded body with high bonding strength.
[0110] Example
[0111] The present invention is not limited to the following embodiments, and may be appropriately modified and implemented within the scope of the above and below-mentioned purposes, which are all included in the technical scope of the present invention.
[0112] [1] Manufacturing Example of the First Manufacturing Method
[0113] In Examples 1 to 3, copper oxide microparticles were produced using the starting materials shown in Table 1. Specifically, ethylene glycol (manufactured by Kanto Chemical) as a solvent, 1-amino-2-propanol (AmIP, manufactured by Kanto Chemical) as an amine compound, and acetic acid (manufactured by Junsei Chemical) as a complexing agent were placed in a reaction vessel, stirred thoroughly, and copper I oxide (Cu 2 O, manufactured by Furukawa Chemical, particle size 0.5-10 μm), or copper oxide II (CuO, manufactured by Nissin Chemical NB-2, particle size 0.1-1 μm).
[0114] Hydrazine hydrate (manufactured by Kanto Chemical) was added as a reducing agent in a water bath in the reaction vessel, and the reaction was carried out while stirring at 1100 rpm. The reaction was carried out in the atmosphere. In order to confirm the difference between laboratory scale and mass production, the starting material was carried out at two levels: 1 g of copper (Examples 1 and 2) and 100 g of copper (Example 3). The obtained product was purified by multiple centrifugal separation using N,N-dimethylacetamide, toluene, and hexane to obtain a slurry containing the product.
[0115] As comparative examples, in Comparative Examples 1 to 3, the starting material was anhydrous copper (II) acetate anhydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and the amount of the amine compound was changed. In Comparative Examples 4 and 5, the starting material was copper oxide, and no complexing agent was added. In Comparative Example 6, except that the reaction vessel was not cooled by a water bath, the same reaction method as in the examples was followed to obtain a slurry containing a product.
[0116] In addition, as shown in Table 1, it was confirmed that when the addition ratio (molar ratio) of the amine compound to copper was 5 times or more, the target Cu 64 O and Cu 8 O is generated rapidly, and in Examples 1 to 3, the amount is 10 times greater.
[0117]
surface
[0118]
[0119] (X-ray diffraction measurement)
[0120] The slurry containing the product was used to perform X-ray diffraction measurement using a powder X-ray diffraction device (XRD, MiniFlexII, D / teX Ultra manufactured by Rigaku Corporation) to obtain the XRD measurement results of the reaction process. The measurement used Cu-Kα radiation and the scanning speed was set to 20° min -1 Regarding Examples 1 to 3, the results are shown in Figure 1 In Comparative Examples 1 to 3, the results are shown in Figure 2 Regarding Comparative Examples 4 to 6, the results are shown in Figure 3 In the XRD measurement results of the reaction process, "0h" indicates when the reducing agent is added, for example, "1h" indicates the measurement result 1 hour after the reducing agent is added. Figure 2 In Comparative Examples 1 to 3, in order to observe the reaction of copper (II) acetate anhydrate as a starting material to Cu 64 O and Cu 8The reaction process of O shows the XRD measurement results of 2θ=0 to 55° including the peak position of copper (II) acetate anhydrate, i.e. 2θ=10°, and in the examples other than Comparative Examples 1 to 3 where the starting material is copper oxide, the XRD measurement results of 2θ=30 to 80° are shown.
[0121] (Electron microscope observation)
[0122] In the electron microscope observation, the obtained product was observed with a scanning electron microscope (SEM, JEOL JSM-6701F, accelerating voltage 15 kV) to obtain a SEM image, and observed with a transmission electron microscope (TEM, JEOL JEM-2000FX, accelerating voltage 200 kV) to obtain a TEM image, and further observed with a scanning transmission electron microscope (STEM, JEM-ARM200F, accelerating voltage 200 kV) to obtain a STEM image. The above observations with TEM and STEM were performed in a state where the microparticles were not agglomerated but dispersed.
[0123] In this manufacturing example, as a result of the electron microscope observation, the TEM images of Examples 1 to 3 show Figure 4 In Example 1 (the starting material is Cu 2 O) STEM image is shown in Figure 5 In the STEM image of Example 2 (the starting material is CuO), Figure 6 middle.
[0124] The above results show that: First, in Example 1 and Example 2, the starting material is 1g of copper, the starting material is copper oxide raw material particles, and acetic acid is added as a complexing agent. Figure 4 A. Figure 4 From the TEM image of B, it can be seen that particles with a diameter of about 5 nm are formed. Figure 1 From the XRD patterns, we can see that these particles contain Cu 64 O and Cu 8 O particles. Figure 5 and Figure 6 The STEM image shows that there is a Cu 64 In Example 3, which is a 100-fold magnification of Example 1, according to Figure 4 TEM images of C and Figure 1 The XRD spectrum of the sample showed that the sample also contained particles with a particle size of about 10 nm, but the sample contained Cu in a similar amount. 64 O and Cu 8 Particles of O.
[0125] In contrast, as in Comparative Examples 1 to 3, when the starting material is copper acetate II, Figure 2The XRD pattern shown in the figure shows that although it contains Cu 64 O and Cu 8 O particles are generated, but the weight and volume of the raw materials are large. In addition, when the starting raw materials are dissolved in the solvent, it is necessary to perform ultrasonic dispersion while stirring manually, which is poor in mass production. In these comparative examples, although acetic acid as a complexing agent is not added, since water and acetic acid are released during the reaction, it can be considered that the same reaction as in the embodiment is carried out. On the other hand, Comparative Examples 4 and 5, in which the starting raw materials are copper oxide raw material particles and acetic acid as a complexing agent is not added, Figure 3 The XRD measurement results of the reaction process are shown in Figure 2, and no Cu 64 O and Cu 8 O, the main product is metallic copper. From these results, it can be seen that acetic acid is required as a complexing agent in the production of copper particles containing trace copper oxide. Figure 5 and Figure 6 In the STEM dark field image shown, a large number of white bright spots were confirmed, indicating the presence of copper clusters of about 0.2 nm.
[0126] From the above, it can be confirmed that the desired Cu-containing nanoparticles can be obtained by using copper oxide particles as the starting material and adding acetic acid as the complexing agent. 64 O and Cu 8 O particles and copper clusters.
[0127] According to the comparison between Example 1 and Example 2, it is preferred to use Cu 2 O as the starting material, the reaction occurs rapidly and the time required for the reaction is shortened. 2 Compared with the prior art using copper acetate II as the starting material, the method using copper acetate II as the starting material reduces the weight of the raw material by 0.4 times and the volume by 0.125 times. In addition, the pre-reaction step, i.e., the step of dissolving copper acetate II in a solvent, is not required, and the handling of the raw material is easier. Therefore, it can be said that this is a manufacturing method with particularly excellent mass productivity.
[0128] In Comparative Example 6, in which the reaction solution was not cooled, the solution temperature rose to a maximum of 53.8°C about 90 minutes after the start of the reaction. At 70 minutes after the start of the reaction, the solution temperature exceeded 50°C, and copper luster began to be seen on the wall surface of the reaction container. Figure 3 As shown in the XRD pattern, Cu 64 O, and no peaks other than copper were confirmed after 2 hours had passed. This shows that it is preferable to cool the reaction solution to 50° C. or lower.
[0129] [2] Production Example of the Second Production Method
[0130] (Preparation of starting materials)
[0131] As copper oxide-coated metallic copper raw material particles with different types of oxide films, copper particles TN-Cu100 (particle size 50-200nm) produced by Taiyo Nippon Sanso, copper particles coated with acetic acid (particle size 50-200nm), and copper particles 07439-01 (particle size 1-10μm) produced by Kanto Chemical were used. These particles were used directly as starting materials, or subjected to the oxidation treatment described below. The copper oxide formed on the surface of the starting material was quantitatively measured by the RIR method of XRD. The results are shown in Table 2. The copper particles produced by Taiyo Nippon Sanso as the starting material in Example 4 are commercially available products, which are characterized by having Cu 2 O layer. Cu can be confirmed 2 The O layer is 1.5 mass %.
[0132] The acetic acid-coated copper particles used as the starting material in Example 5 are manufactured by a liquid phase reduction method according to the following method. 1 mol of copper oxide II (NB-2 manufactured by Nissin Chemical) is added as a raw material, 1 L of ethylcarbitol (manufactured by Sankyo Chemical) is added as a solvent (ethylcarbitol) and 60 mmol of acetic acid is added as a protective agent. After the temperature is raised to 70°C, 2 mol of hydrazine hydrate (manufactured by Kanto Chemical) is added and reacted for 1 hour while stirring. After the reaction, purification is performed twice using acetone and methanol, and copper powder is obtained by vacuum drying. The obtained copper powder is subjected to an oxidation treatment by exposure to air at room temperature for 44 hours to obtain a Cu 2 The copper fine particles of the O layer were the acetic acid-coated copper particles used as the starting material in Example 5. In addition, since oxidation of copper on the surface of the acetic acid-coated copper particles was suppressed, it is considered that acetic acid existed on the surface.
[0133] The copper particles manufactured by Kanto Chemical used as the starting material in Examples 6 to 8 are also commercially available products. No oxides were detected by XRD in the initial state, but it can be considered that the surface was slightly naturally oxidized. In Example 6, the copper raw material particles with slightly naturally oxidized surfaces were used as the starting material. In Example 7, as an oxidation treatment, the powder of the copper particles manufactured by Kanto Chemical was placed in a constant temperature and humidity chamber maintained at 80% RH at 80°C and exposed for 48 hours, and the copper oxide-coated metal copper raw material particles with a CuO layer of 1.1% by mass were used as the starting material. In addition, in Example 8, as another oxidation treatment, 0.5 mol of the copper particles manufactured by Kanto Chemical were placed in 500 g of ultrapure water, heated and boiled at 100°C for 90 minutes, and a CuO layer of 3.4% by mass was formed. 2 O-layer copper oxide-coated metallic copper raw material particles are used as starting materials.
[0134] (Manufacturing of core-shell microparticles)
[0135] Using the above starting materials, the reaction is carried out using the solvents etc. in the addition amounts shown in Table 2. Specifically, ethylene glycol (manufactured by Kanto Chemical) is used as a solvent, 1-amino-2-propanol (AmIP, manufactured by Kanto Chemical) is used as an amine compound, and acetic acid (manufactured by Junsei Chemical) is used as a reaction vessel, and after sufficient stirring, the above starting materials are added. In a state where the reaction vessel is water bathed, hydrazine hydrate (manufactured by Kanto Chemical) is added as a reducing agent, and the reaction is allowed to proceed while stirring at 1100 rpm. The reaction is carried out in the atmosphere. After the reaction, N,N-dimethylacetamide, toluene, and hexane are used for purification by multiple centrifugal separations to obtain a slurry containing the product. As a comparative example, in Comparative Example 7, except that no complexing agent is added, a slurry containing the product is obtained in the same manner as in Example 4.
[0136]
surface
[0137]
[0138] (X-ray diffraction measurement)
[0139] Using the slurry containing the product, X-ray diffraction measurement of the reaction process was performed in the same manner as in the production example of the first production method [1]. Regarding Examples 4 to 6, the results are shown in Figure 7 In Example 7, Example 8 and Comparative Example 7, the results are shown in Figure 8 middle.
[0140] (Electron microscope observation)
[0141] The obtained product was used to perform SEM observation, TEM observation, and STEM observation in the same manner as in the production example of the first production method [1] above.
[0142] Based on the above X-ray diffraction measurement and electron microscope observation, the following can be confirmed for each example. First, regarding Example 4, according to Figure 7 In the XRD pattern of the reaction process, in the example where the starting material is a 50-200 nm Taiyo Nippon Sanso copper particle with an oxide film of 1.5 mass % and acetic acid, in addition to the starting material copper, Cu 64 O and Cu 8 O generation. The SEM images of the starting material of Example 4 and the particles after 24 hours of reaction show Fig. 9 middle. Fig. 9 A represents the starting material, Fig. 9B represents the reaction time of 24 hours. Comparison of these photos shows that, through the reaction, micro-oxides that are believed to be generated are attached around the copper raw material particles of the starting material. In addition, the TEM image of the particles obtained in Example 4 is shown in Fig.10 In addition, the STEM image of the particles obtained in Example 4 is shown in Fig.11 In. By Fig.10 The TEM image confirms that the generated particles are core-shell in shape. Fig.11 The lattice spacing confirmed in the STEM image shows that the core is copper and the surface of the core is covered with Cu particles with a diameter of about 3nm. 64 O and Cu 8 The nanoparticles of O are covered in a shell shape.
[0143] On the other hand, in Comparative Example 7, which was reacted under the same conditions as Example 4 except that acetic acid was not added, no Cu was detected. 64 O and Cu 8 O, the product is only metallic copper. This confirms that acetic acid is required as a complexing agent in the production of the oxide-containing particles of the present embodiment.
[0144] Next, regarding Example 5, according to Figure 7 The XRD spectrum of the reaction process can confirm that when the copper oxide-coated metallic copper raw material particles having an oxide film of 2.2 mass % are used as the starting material, Cu is also generated in addition to the copper of the starting material as in Example 4. 64 O and Cu 8 O. The SEM images of the starting material of Example 5 and the particles after 24 hours of reaction are shown in Fig.12 middle. Fig.12 A represents the starting material, Fig.12 B represents the reaction time of 24 hours. In addition, the TEM image of the particles obtained in Example 5 is shown in Fig.13 From these SEM images and TEM images, it can be confirmed that the surface of the core copper particles is covered with Cu 64 O and Cu 8 O nanoparticles are covered in a shell shape.
[0145] Examples 6 to 8 are examples using copper particles manufactured by Kanto Chemical. Figure 7 and Figure 8 The XRD patterns of the reaction process confirmed that Cu was generated regardless of whether the copper particles produced by Kanto Chemical were oxidized or not. 64 O and Cu 8 O. In addition, the TEM image of the particles obtained in Example 6 shows Fig.14 The SEM images of the starting material of Example 7 and the particles after 24 hours of reaction are shown in Fig.15 middle. Fig.15 A represents the starting material, Fig.15 B represents the reaction time of 24 hours. The TEM image of the particles obtained in Example 7 is shown in Fig.16 In addition, the SEM images of the starting material of Example 8 and the particles after 24 hours of reaction are shown in Fig.17 middle. Fig.17 A represents the starting material, Fig.17 B indicates after 24 hours of reaction. Figure 14 to Figure 17 As shown, it can be confirmed that the surface of the core copper particles contains Cu 64 O and Cu 8 O nanoparticles are covered in a shell shape.
[0146] Based on the above confirmation, the following explanation can be made. In the above Examples 1 to 3, Cu is efficiently generated from copper oxide. 64 O and Cu 8 In order to effectively generate core-shell particles having a shell containing slightly oxidized copper, it is preferred that the starting material is a copper oxide-coated metallic copper raw material particle having a surface oxide layer. In Example 6 having a surface oxide layer having a degree of natural oxidation that cannot be detected by XRD, according to Fig.14 The TEM image shown in the figure also confirms that a sufficient shell has been formed. 2 O is a natural oxidation film that cannot be detected by X-ray diffraction. It is desirable to form a thick layer of Cu in the core-shell type micro-copper oxide coated copper particles. 64 O and Cu 8 When the surface of the copper particles is positively oxidized, as in Examples 5, 7 and 8, thick-shelled copper-coated copper particles can be formed.
[0147] In addition, the RIR quantitative measurement results of the particles obtained in Examples 4 to 8 show that due to Cu 64 O and Cu 8 Since the quantitative value of O is greater than the amount calculated from the amount of oxides contained in the starting material, oxidation and complexation of the metal copper particles as the starting material occur in the reaction solution, and Cu 64 O and Cu 8 O generated by the reaction.
[0148] In the core-shell particles having a shell of slightly oxidized copper, if it is desired to form a thick shell with particles having a small core particle size and a large surface area ratio, the starting material needs to have a larger surface oxide layer, and it is desirable to have a surface oxide layer of 1.5% to 2.2% by mass as in Examples 4 and 5.
[0149] From the above, it can be confirmed that when core-shell particles having a shell of slightly oxidized copper are generated, 2 By using copper particles coated with copper oxides of one or more of CuO and CuO as starting materials and adding acetic acid as a complexing agent, core-shell type micro-copper oxide-coated copper particles can be obtained, which have copper particles as cores and CuO particles with a particle size of less than 20 nm. 64 O and Cu 8 According to this method, it is possible to easily obtain core-shell type micro-copper oxide coated copper microparticles in which the surface of submicron to micron-sized copper particles is covered with nanoparticles containing micro-copper oxide, which is impossible to achieve with conventional mixing methods.
[0150] In the method of this embodiment, not only submicron copper particles but also micron-sized copper particles can be obtained, that is, core-shell type micro-oxide copper-coated copper particles can be obtained, in which the surface of micron-sized copper particles is covered with nanoparticles containing micro-oxide copper. In addition, the micro-oxide copper-coated copper particles of this embodiment have the advantages of being easy to precipitate because the micro-oxide copper particles are attached to the copper particles as the core, and the particles can be easily recovered during purification.
[0151] The copper paste containing the slightly oxidized copper-coated copper particles of this embodiment is formed by Cu 64 O and Cu 8 The shell composed of nanoparticles of O is easily reduced to metallic copper, and the adjacent copper microparticle cores are closely connected to each other, thereby greatly promoting the sintering between the core particles. The obtained sintered body becomes a structure in which the copper microparticle cores with high crystallinity are closely connected, and it is expected to show excellent mechanical strength and high conductivity.
[0152] [3] Another manufacturing example of the second manufacturing method (Example 4A)
[0153] Example 4A is an example in which the synthesis scale of Example 4 was changed.
[0154] (Manufacturing of core-shell microparticles)
[0155] The synthesis of the core-shell type copper oxide coated copper microparticles used in this manufacturing example was carried out in the same manner as in Example 4, except that the amount of the starting material, 1-amino-2-propanol (AmIP), acetic acid, hydrazine hydrate and ethylene glycol (EG) added was 100 times, respectively, to obtain a slurry containing copper oxide coated copper microparticles as a product in hexane. The weight of the copper oxide coated copper microparticles in the slurry was calculated in advance by the following formula (1).
[0156] [Formula 1]
[0157]
[0158] In formula (1),
[0159] Y: Particle weight in slurry (g)
[0160] M s : Slurry weight (g)
[0161] V s :Slurry volume (cm 3 )
[0162] ρ m : Solvent density (g / cm 3 )
[0163] ρ Cu : Copper density (g / cm 3 )
[0164] (Manufacturing of paste containing core-shell microparticles)
[0165] The solvent of the slurry containing the synthesized micro-copper oxide coated copper microparticles was replaced from hexane to ethanol by centrifugal separation. The slurry was centrifuged again to remove the ethanol supernatant to obtain a wet cake of micro-copper oxide coated copper microparticles. 7.5 parts by weight of triethanolamine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to 92.5 parts by weight of micro-copper oxide coated copper microparticles in the wet cake (value calculated by formula (1)). After addition, stirring was performed for 4 minutes using an autorotating revolution mixer (AR-100 manufactured by THINKY Corporation), and then, dispersion treatment was performed intermittently for 3 minutes using a thin film rotating high-speed mixer (FILMIX 56-L manufactured by PRIMIX) to obtain a dispersed paste. The obtained dispersed paste was divided into small portions, and different amounts of triethanolamine were added to each portion to adjust the concentration, and stirred for 8 minutes using an autorotating revolution mixer. Thereafter, the mixture was kept in a vacuum at room temperature until the weight no longer changed to remove the ethanol, and 5 levels of pastes with different concentrations of micro-copper oxide coated copper microparticles were obtained.
[0166] The paste was subjected to thermogravimetric differential thermal analysis (TG-DTA) using a TG / DTA simultaneous measurement device manufactured by Shimadzu Corporation in a 3% hydrogen-nitrogen mixed gas atmosphere at a heating rate of 5°C / min. The results are shown in Fig.18 In. From Fig.18 The weight reduction shown by TGA can confirm that the five levels of pastes obtained contain 91.3 wt%, 89.8 wt%, 87.6 wt%, 84.4 wt%, and 83.0 wt% of micro-oxide copper-coated copper microparticles, respectively. Hereinafter, the concentration of micro-oxide copper-coated copper microparticles contained in the paste is referred to as "paste concentration".
[0167] (Joint firing evaluation)
[0168] Using the obtained paste, two copper test pieces were pasted together to prepare a sample for evaluation of fired bonding bonded by firing the paste, and the bonding strength was measured.
[0169] 1. Preparation of samples for evaluation of bonding firing
[0170] The production process of the sample for evaluation of bonding firing is as follows Fig.19 First, from the oxygen-free copper plate (C1020P) with a thickness of 5 mm, as shown in Fig. 20A As shown in the figure, copper test pieces 1 with a diameter of 12 mm and copper test piece 2 with a diameter of 5 mm were cut out as circular copper test pieces. The surface of each copper test piece was polished with water-resistant sandpaper (SiC paper) P4000, and then mirror-finished (polished) with a polishing cloth impregnated with a 0.5 μm aluminum oxide powder suspension, and then degreased. Before applying the paste, each copper test piece was immersed in 2.5M hydrochloric acid to remove the copper oxide film on the surface, and then fully washed with pure water and methanol and dried.
[0171] Next, metal mask printing is performed. In detail, it is to use Fig. 20B The size of the opening portion schematically shown in FIG. 1 is a metal mask having a diameter of 5 mm and a thickness of 0.15 mm. Fig. 20C As shown in the figure, the above paste (containing 91.3% by weight of micro-oxide copper-coated copper particles) 3 is applied to the center of a copper test piece 1 with a diameter of 12 mm, and the paste is bonded to a copper test piece 2 with a diameter of 5 mm. Then, the two bonded copper test pieces are pressed along the edges of the two bonded copper test pieces by a hot press. Fig. 20C A load of 15 MPa is applied in the direction of the arrow, and the temperature is raised to 200°C at a high speed of 90°C / min. After reaching 200°C, the temperature is maintained to sinter the paste. The holding time after reaching 200°C is 1 minute, 5 minutes, 10 minutes or 15 minutes. After being maintained at 200°C, it is removed from the hot press and rapidly cooled to room temperature to obtain a sample for joint sintering evaluation, which is formed by bonding copper test pieces to each other by the sintered product formed by sintering the paste. In addition, a series of operations from metal mask printing to the above-mentioned sintering and rapid cooling to room temperature are carried out in a nitrogen atmosphere.
[0172] 2. Joint firing evaluation test (measurement of bonding strength)
[0173] The bonding strength of the samples for evaluation of the bonding firing was evaluated using a 5 kN material testing machine (manufactured by Shimadzu Corporation). Fig.20DIn the schematic cross-sectional view shown in FIG, a load was applied parallel to the coating surface at a speed of 1 mm / min to the tester's fixing fixture 4 to measure the breaking load of the copper test piece as the bonding strength. The results are shown as a graph showing the relationship between the holding time (bonding time) after reaching the above 200°C and the breaking load (bonding strength). Fig.21 middle. Fig.21 The vertical width shown in each measurement value indicates the deviation of 2 to 4 measurements. Fig.21 As shown, when the bonding time is more than 5 minutes, an extremely high bonding strength of more than 66 MPa can be obtained. In addition, even if the bonding time is 1 minute, a sufficient bonding strength of 47 MPa can be obtained.
[0174] The SEM image of the fracture surface of the test sample for evaluation of the bonding sintering with a bonding time of 1 minute shows Fig. 22 In. Fig. 22 It can be confirmed that the particles are tightly sintered. In addition, the temperature distribution of the hot press when the bonding time is 1 minute is shown in Fig.23 In. Fig.23 As shown, when the bonding time is 1 minute, the bonding process is a short process of about 8 minutes from the start of heating to cooling. This proves that if the paste containing the micro-oxide copper-coated copper particles of this embodiment is used, a firmly sintered product can be obtained even in such a very short time.
[0175] (Electrical conductivity evaluation)
[0176] Cut an alumina plate (AO-5050 made by Furuuchi Chemical) with a thickness of 1mm to make it 5cm×2.5cm as a substrate for evaluation. Use a scraper (made by Imoto Manufacturing) with a coating width of 2cm and a coating thickness of 10μm to apply the above-mentioned 5 levels of paste with different concentrations (paste concentration) of the micro-copper oxide-coated copper particles on the surface of the substrate in a range of 2cm wide and 4cm long. Put it into a tubular furnace, and supply nitrogen or 3% hydrogen / nitrogen mixed gas into the tube at a flow rate of 1L / min, and perform gas replacement at room temperature for more than 30 minutes. Thereafter, while supplying nitrogen or 3% hydrogen / nitrogen mixed gas into the tube at a flow rate of 1L / min, it takes about 20 minutes to heat up to the evaluation temperature of 200°C, and after maintaining the evaluation temperature of 200°C for 1 hour, it is naturally cooled to room temperature to obtain a substrate with the above-mentioned paste fired. When the paste concentration was 91.3% by weight, the evaluation temperature was 150°C, 200°C, and 250°C. The dark brown paste at the time of application turned reddish brown after firing. In addition, the series of operations from the application of the above-mentioned paste to the holding at the evaluation temperature and the natural cooling to room temperature were all carried out in a nitrogen atmosphere.
[0177] The conductivity of the fired product was measured using a resistivity meter (Loresta GP, ASP probe manufactured by Mitsubishi Chemical Analytical Science). The relationship between the paste concentration and the volume resistivity at different evaluation temperatures is shown in the graph together with the volume resistivity of the bulk copper. Fig.24 In. According to Fig.24 The volume resistivity of the fired product using 91.3% by weight of the paste is 6×10 -6 Ωcm, which is similar to the resistivity of bulk copper at 0°C (1.55×10 -6 When measuring the volume resistivity, the resistivity correction factor RCF, which corrects the shape factor of the coating film, uses the value calculated by LorestaGP, and the film thickness of the fired product is calculated from the cross-section formed by the fracture of the fired substrate observed with a microscope (Keyence digital microscope VHX-7000).
[0178] (X-ray diffraction measurement) (XRD measurement results before and after sintering)
[0179] Using a powder X-ray diffraction device (XRD, Rigaku MiniFlexII, D / teX Ultra), X-ray diffraction measurements were performed before and after the paste was fired, and the XRD measurement results of the reaction process when fired at 250°C in a 3% hydrogen / nitrogen mixed gas were obtained. The results are shown in Fig.25 In. Fig.25 As shown, the Cu in the coating paste before firing is 64 O and Cu 8 The broad peak of O disappears due to reduction after firing, and only a sharp peak derived from copper is confirmed. Fig.26 This is a SEM image of a product fired at 250°C in a 3% hydrogen / nitrogen mixed gas. Fig.26 The photographs confirm that the sintered product can be obtained with densely sintered particles. 64 O and Cu 8 O is a nano-sized particle formed in a shell-like shape on the surface of the copper particle, which suggests that during the reduction process, the melting point is lowered, resulting in efficient sintering of adjacent copper particles, proving that the slightly oxidized copper-coated copper particles of this embodiment have high sinterability.
[0180] [4] Another manufacturing example of the second manufacturing method (Example 9)
[0181] (Preparation of copper powder)
[0182] As the starting material, the metal copper particles used were hexanoic acid-coated copper particles (particle size 30-100 nm). The hexanoic acid-coated copper particles were prepared by the liquid phase reduction method according to the following method. 1 mol of copper oxide II (NB-2 manufactured by Nissin Chemical) was added as a raw material, 1L of ethanol (manufactured by JAPAN ALCOHOL TRADING) as a solvent, and 60 mmol of hexanoic acid as a protective agent. After heating to 70°C, 2 mol of hydrazine hydrate (manufactured by Kanto Chemical) was added and reacted for 1 hour while stirring. After the reaction, the mixture was purified twice with acetone and methanol, and vacuum dried to obtain copper powder.
[0183] (Addition of copper oxide powder and production of core-shell microparticles)
[0184] The addition of copper oxide powder to copper powder and the generation of core-shell particles were carried out according to the following process. 222.9 mmol of ethylene glycol (produced by Kanto Chemical) as a solvent, 157 mmol of 1-amino-2-propanol (AmIP, produced by Kanto Chemical) as an amine compound, and 78.5 mmol of acetic acid (produced by Junsei Chemical) as a complexing agent were placed in a reaction container, and after sufficient stirring, 15.7 mmol (0.998 g) of hexanoic acid-coated copper particles as a starting material and copper I oxide (Cu I) as an additive were added. 2 O, manufactured by Furukawa Chemical, particle size 0.5-10 μm) 0.367 mmol (0.0525 g). The amount of copper oxide I added to the starting material (the total amount of metallic copper and copper oxide) was 5% by mass. Hydrazine hydrate (manufactured by Kanto Chemical) was added as a reducing agent in a water bath in the reaction vessel, and the reaction was carried out while stirring at 1100 rpm. The reaction was carried out in the atmosphere. After the reaction, N,N-dimethylacetamide, toluene, and hexane were used for purification by multiple centrifugal separations to obtain a slurry containing the product.
[0185] (X-ray diffraction measurement)
[0186] The obtained product was subjected to X-ray diffraction measurement in the same manner as in the above-mentioned Example 1 of the first production method. The results are shown in Fig. 27 middle.
[0187] (Electron microscope observation)
[0188] The obtained product was observed by SEM and TEM in the same manner as in the above-mentioned Example 1 of the first production method. As a result, the SEM image showed Fig.28 middle. Fig.28 A represents the starting material, Fig.28 B represents the reaction time of 24 hours. Fig.29 middle.
[0189] According to the Fig. 27The XRD pattern of the reaction process shown in the figure confirms that in addition to copper, there is also Cu 64 O and Cu 8 O is generated. Fig.28 Comparison of the SEM images of A (starting material) and B (after 24 hours of reaction) shows that the copper particles of the starting material are attached to the copper particles due to the reaction. 64 O, Cu 8 O is a micro-oxide. In addition, according to Fig.29 The TEM image shows that the surface of the core copper particles is covered with Cu 64 O and Cu 8 O nanoparticles are covered in a shell shape.
[0190] In the production example of the second production method [2], copper particles having a surface oxide layer are used as the starting material. However, the above results confirm that, even when copper oxide particles are separately added to the copper particles as the core, core-shell type micro-copper oxide-coated copper particles can be obtained, which have copper particles as the core and Cu particles having a particle size of 20 nm or less. 64 O and Cu 8 In Example 9, copper oxide particles were used as an additive, but as long as copper complex ions are formed in the reaction solution, it is also considered that Cu 64 O, Cu 8 Therefore, as a compound added to the core particle, copper complex salts other than copper oxide can also obtain the same effect.
[0191] Industrial Applicability
[0192] The copper oxide-containing particles of this embodiment can be fully sintered at a relatively low temperature of 200°C or less even under normal pressure (or pressures above it), and a sintered body showing sufficient electrical conductivity can be obtained. Therefore, the copper oxide-containing particles of this embodiment can be used as a chip bonding material for power semiconductors in heat conduction applications, in addition to circuit forming materials and other micro-wiring materials for printed circuit boards (especially flexible circuit boards). In addition, they can also be used as antistatic materials, electromagnetic wave shielding materials, infrared blocking materials, etc.
[0193] The present application claims priority based on Japanese Patent Application Nos. 2022-140366 and 2023-018736, which are incorporated herein by reference.
[0194] Description of Reference Numerals
[0195] 1, 2 Copper test piece
[0196] 3 Paste containing micro-oxide copper coated copper particles
[0197] 4 Fixtures for fixing the testing machine
Claims
1. A method for producing a particle containing a trace amount of copper oxide, wherein the particle containing a trace amount of copper oxide has at least Cu 64 O and Cu8O, one or more micro-oxidized copper, wherein include: Preparing raw material particles having copper oxide containing at least one of CuO and Cu2O on the surface; and The raw material particles are mixed with a solution containing an amine compound and a complexing agent, and then a reducing agent is added to carry out a reaction in an oxygen-containing atmosphere.
2. The manufacturing method according to claim 1, wherein: The raw material particles are raw material particles containing copper oxide containing one or more of CuO and Cu2O.
3. The manufacturing method according to claim 1, wherein: The raw material particles are copper oxide-coated copper raw material particles having a copper raw material particle as a core and a copper oxide coating containing one or more of CuO and Cu2O as a shell.
4. The production method according to any one of claims 1 to 3, wherein The copper oxide contained in the raw material particles is Cu2O.
5. The production method according to any one of claims 1 to 4, wherein The complexing agent is a carboxylic acid.
6. The production method according to any one of claims 1 to 5, wherein The complexing agent is acetic acid.
7. The production method according to any one of claims 1 to 6, wherein The reaction is carried out below 50°C.
8. The production method according to any one of claims 1 to 7, wherein The average particle size of the raw material particles is greater than 20 nm and less than 10 μm.
9. A slightly oxidized copper-coated copper particle comprising a copper particle as a core and a Cu 64 A shell of one or more micro-oxidized copper among CuO and Cu8O.
10. The micro-copper-oxide-coated copper particles according to claim 9, wherein: The Cu 64 The micro-oxide copper particles of at least one of CuO and Cu8O are micro-oxide copper particles having an average particle size of more than 1 nm and less than 20 nm.
11. The micro-copper oxide-coated copper particles according to claim 9 or 10, wherein: The copper particles serving as the core have an average particle size of more than 20 nm and less than 2 μm. 12 . A bonding material comprising the slightly-oxidized copper-coated copper particles according to claim 9 .
Citation Information
Patent Citations
Copper oxide particle composition, conductive paste, and conductive ink
JP2020029392A
Copper cluster, mixed particles, conductive paste, and conductive ink
JP2020100893A
Aggregation of multi-source health-based safety information in graphical user interface
JP2022140366A
Controller and medium processor
JP2023018736A
Oxide-containing copper fine particles, method for manufacturing same, and method for manufacturing sintered compact using oxide-containing copper fine particles
WO2022045252A1